Comparing the drivers of medical student emigration intention across two African nations. - Chaet, Alexis; Fessehaie, Nathaniel; Rajaguru, Praveen R.; Alavi Jusabani, Mubashir; Randaoharison, Pierana; Samison, Luc; Anderson, Ursula; Ramanantoanina, Prisca; Zafimar, Mosa; Numfor, Anchi; Hardaker, W. Mack; Massawe, Honest; et al. (Medical Education, 2021)
Background: Sub‐Saharan Africa faces the highest relative need for health care workers in the world and the emigration of physicians significantly contributes to this deficit. Few studies have explored development of these patterns during medical education. This study investigates career aspirations of medical students in two African nations with similar Human Development Indices, but distinct differences in training structure to better inform retention strategies. Methods: A cross‐sectional survey was administered in 2018 to medical students in Madagascar (University of Antananarivo, University of Mahajanga) and Tanzania (Kilimanjaro Christian Medical College, KCMC). Outcomes included emigration/career intentions, and factors influencing these decisions. Analysis utilised chi‐square and Fisher's exact tests (α < 0.05, two‐tailed) for statistical differences, logistic regression and qualitative content analysis of free text data. Results: A total of 439 students responded to the survey with a response rate of 12.9% from Antananarivo (n = 142/1097), 11.6% from Mahajanga (n = 43/370), and 60.0% from KCMC (n = 254/423). Significantly more Malagasy (49.7%, n = 90/181) than Tanzanian (25.2%, n = 54/214) students expressed emigration intent (P <.001). Malagasy students indicating research, possibility of working abroad, or work intensity as influencing career choice more frequently expressed a desire to emigrate. Satisfaction with computer/internet access was inversely correlated with a desire to work abroad. In comparison, Tanzanian students reporting income potential as influential in their career choice or attending a private high school were more likely to express a desire to work abroad. Qualitative content analysis of free text data demonstrated deficits in faculty availability, diversity of training locations and a particular emphasis on infrastructure challenges within Madagascar. Interpretation: A significant number of students desire to work abroad. Emigration interests are influenced by access to postgraduate training, infrastructure and opportunities in academia, which differ across countries. Efforts to retain physicians should consider these country and institution‐specific factors that influence medical student desire to emigrate. Fessehaie et al. reveal that drivers of student emigration differ across institutions, suggesting that efforts to retain physicians must be tailored to country and institution‐specific contexts.